Natural capital in practice: How to include its value in Dutch decision-making processes - Ruijs, Arjan; van Egmond, Petra (Ecosystem services, 2017)
•Sustainable use of natural capital is promising in three decision-making domainst.•In each domain, natural capital is operationalized and mainstreamed differently.•Mainstreaming natural capital in decisions leads to innovation and new cooperations. Scientific and policy attention for natural capital and ecosystem services have grown fast during the last decade. As a result, awareness on the value of the stock of natural capital and the flow of ecosystem services it provides increased. Decision-makers from governments, business and nature organisations nowadays have much better insights into the opportunities its sustainable use provides, for themselves and for society. Yet, translating lessons from natural capital research to policy remains complex. In this paper, on the basis of the results of the two-year Natural Capital Netherlands programme, it is elaborated how, in practice, governments, businesses and nature organisations can include the value of natural capital in their decision-making processes. The planning and decision-making processes studied in this programme can be clustered into three domains: sustainable entrepreneurship, entrepreneurial nature management and area development. For each domain of decision-making, the approach to be followed differs somewhat and different policies should be developed to reach the situation in which it is mainstream to include the value of natural capital in decision-making. Moreover, it is shown that incorporating natural capital leads to innovation, with new market opportunities, new nature development and new collaborations between various parties as a result.